Prime and boost aerosol exposure via fog machine or shisha smoke followed by cinnamon hypersensitivity and anaphylaxis to spiced food. Issue 1 (December 2016) - Jensen-Jarolim, Erika; Roth-Walter, Franziska; Leitner, Erich; Buchleitner, Stefan; Vogelsang, Harald; Kinaciyan, Tamar
Abstract Background Cinnamon aldehyde (alias cinnamaldehyde) is widely used in food, textile or cosmetic industry. It is mostly associated with contact allergy, but immediate type allergies have been reported. The present study was triggered by a case of anaphylactic events to cinnamon in food and upon skin prick test. We investigated a possible correlation of exposure to a disco fog machine and/or shisha consumption with immediate type hypersensitivity to cinnamon aldehyde in the patient and healthy volunteers. Methods & Results In both fog machines and shisha pipes heating of glycerol-based fluids before evaporation renders chemical transversion to malodorous acrolein. Therefore, both methods are frequently operated with aroma additives. Cinnamon aldehyde and derivatives could be detected by gas chromatography in sampled fog flavored with cola fragrance. The patient as well as healthy (mostly female) volunteers were skin prick tested using cinnamon aldehyde diluted in 0.9 % NaCl, Vaseline® or fog fluid. Persons with a history of exposure to disco fog or shisha (n = 10, mean 32.8 years) reacted with a significantly larger wheal and flare reaction in the skin test (p = 0.0115, p = 0.0146, orp = 0.098) than the non-exposed (n = 8, mean 37.3 years). Both groups were gender matched, but differed in the mean age by 4.5 years. This reaction was specific as compared to skin reactivity to cinnamon alcohol, with only a trend to higher reactivity in exposed persons (ns). Conclusion From our data we conclude that hapten fragrances such as cinnamon aldehyde may during heating in glycerol fluids associate to complete antigens and via inspiration lead to specific immediate type hypersensitivity. In some cases the hypersensitivity may be unmasked by spiced food containing cinnamon aldehyde or related chemicals, and lead to severe adverse reactions.